VIBRATING PROTECTION SYSTEM OF THE WORKPLACE OF THE OPERATOR OF THE KNOCK-OUT LATTICE FOR BRANCH OF THE FORMING MIX - A.V. MOZGOVOY (Advanced Engineering Research, 2008)
The methodology of modeling and optimization of vibrating protection systems of a workplace of the operator of a knock-out lattice for branch by a vibrating method of a forming mix in foundry manufacture is considered.